Contact allergy induced by bisphenol A diglycidyl ether leachables from aluminium tubes for pharmaceutical use - Breuer, K.; Lipperheide, C.; Lipke, U.; Zapf, T.; Dickel, H.; Treudler, R.; Molin, S.; Mahler, Vera; Pfoehler, C.; Loeffler, H.; Schwantes, H.; Schnuch, A. (Allergy, 2015)
Aluminium tubes for pharmaceutical use are internally lacquered with epoxy resins (ER) based on bisphenol A diglycidyl ether (BADGE). Recently, it was shown that remnants of ER polymerization like BADGE are extractable from epoxy-based coatings of commercially available tubes and may leach into semi-solid drug preparations. We aimed to evaluate the safety of BADGE-contaminated macrogol ointments in individuals sensitized to ER based on BADGE by use tests.Repeated open application testing (ROAT) in 11 patients sensitized to ER based on BADGE with BADGE in macrogol ointments (3 mg/kg; 30 mg/kg, equivalent to BADGE concentration determined in macrogol ointment after storage in a commercially available tube; 300 mg/kg).The 30 mg/kg BADGE ointment elicited reactions in three patients, and another three patients reacted to 300 mg/kg BADGE ointment. No reactions to the vehicle control and 3 mg/kg BADGE were observed.Elevated BADGE concentrations in ER-coated aluminium tubes pose a risk of developing contact dermatitis to patients sensitized to ER based on BADGE. Quality standards are deemed necessary for the production of ER-coated aluminium tubes intended for pharmaceutical use and should consider the results of the present ROAT study.
EVALuna2:19547